Historians across borders writing American history in a global age - Barreyre, Nicolas; Heale, Michael; Tuck, Stephen; Vidal, Cecile (University of California Press, 2014)
In this stimulating and highly original study of the writing of American history, twenty-four scholars from eleven European countries explore the impact of writing history from abroad. Six distinguished scholars from around the world add their commentaries. Arguing that historical writing is conditioned, crucially, by the place from which it is written, this volume identifies the formative impact of a wide variety of institutional and cultural factors that are commonly overlooked. Examining how American history is written from Europe, the contributors shed light on how history is written in the.